The Effectiveness Of Mindfulness-Based Behavior - Cognitive Therapy In Reducing Symptoms Of Depression In People With Persistent Depression - Rajabpouranvar, Nazli; Hatami, Mohammad; Rezini, Hadi Hashemi (The Turkish Online Journal of Design Art and Communication, 2016)
Introduction: persistent depression disorder is a common problem and mindfulness-based cognitivebehavioral therapy has considered as effective treatments in this field. Objective: The aim of this study was to assess the effectiveness of mindfulness-based behavior - cognitive therapy in reducing symptoms of depression in people with persistent depression. Method: Two patients with persistent depression were selected through convenience sampling. Each six times by the mindfulness questionnaire (FFMQ) Bauer, emotion regulation difficulties questionnaire (DERS) and Beck Depression Inventory (BDI-II) were evaluated. The study use single participants multiple baselines, the data collected using repeated measures analysis and data analysis using graphs were analyzed. Formula cure rate and recovery detection criteria for judging the recovery rate was applied. Results: participants with persistent depressive disorder with high percentages of recovery in the post-treatment and 30-day follow-up study proved its effectiveness in all the variables. Conclusion: Mindfulness-based behavior-cognitive therapy in reducing symptoms of depression in people with persistent depression is effective. Therefore, clinicians should attend it more.
Keywords: Cognitive therapy; mindfulness; Cognitive emotion; persistent depression disorder